2016
DOI: 10.1160/th15-02-0119
|View full text |Cite
|
Sign up to set email alerts
|

The D173G mutation in ADAMTS-13 causes a severe form of congenital thrombotic thrombocytopenic purpura

Abstract: The D173G mutation in ADAMTS-13 causes a severe form of congenital thrombotic thrombocytopenic purpura KAUST Repository

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…In both shear flow assays, we have found that sufficient VWF proteolysis could be achieved by almost all variants at 10% of the normal plasma concentration. Our data thus confirm previous suggestions that impaired secretion is the disease-causing variable for most variants [26,48,49]. Out of the variants investigated here, only p.Asp235Tyr and p.Arg349Cys exhibit significant residual secretion but strongly reduced activity under static as well as flow conditions (Table 1).…”
Section: Plos Onesupporting
confidence: 92%
“…In both shear flow assays, we have found that sufficient VWF proteolysis could be achieved by almost all variants at 10% of the normal plasma concentration. Our data thus confirm previous suggestions that impaired secretion is the disease-causing variable for most variants [26,48,49]. Out of the variants investigated here, only p.Asp235Tyr and p.Arg349Cys exhibit significant residual secretion but strongly reduced activity under static as well as flow conditions (Table 1).…”
Section: Plos Onesupporting
confidence: 92%
“…However, a greater prevalence has been observed in the Central Norway Health Region, where the estimated prevalence of the p.R1060W mutation is 16.7 cases per million people [52]. More than 200 ADAMTS13 mutations have been identified in all of the ADAMTS13 protein domains [53][54][55]. Of note, some missense ADAMTS13 single-nucleotide polymorphisms have also been identified, which, in some cases, are in strong linkage disequilibrium with specific ADAMTS13 mutations, influencing their molecular effects [56][57][58].…”
Section: Clinical Symptoms Of First Episodes and Relapse Incidence Of...mentioning
confidence: 99%
“…Thus, <10% ADAMTS13 activity is used as a cut-off for diagnosing TTP patients (43). ADAMTS13 deficiency in TTP is generally associated with the formation of autoinhibitory ADAMTS13 antibodies; however, it can also be caused by mutations in the ADAMTS13 gene (31,(44)(45)(46)(47). Although TTP is not a common critical illness, its pathophysiology serves as an archetype for microvascular thrombosis caused by an imbalance in ADAMTS13 and VWF.…”
Section: Associations Between Vwf and Adamts13 In Diseasementioning
confidence: 99%